Passivation of photonic nanostructures for crystalline silicon solar cells. (1st April 2014) - Trompoukis, Christos; El Daif, Ounsi; Pratim Sharma, Parikshit; Sivaramakrishnan Radhakrishnan, Hariharsudan; Debucquoy, Maarten; Depauw, Valerie; Van Nieuwenhuysen, Kris; Gordon, Ivan; Mertens, Robert; Poortmans, Jef
Abstract: We report on the optical and electrical performances of periodic photonic nanostructures, prepared by nanoimprint lithography (NIL) and two different etching routes, plasma, and wet chemical etching. Optically, these periodic nanostructures offer a lower integrated reflectance compared with the industrial state‐of‐the‐art random pyramid texturing. However, electrically, they are known to be more challenging for solar cell integration. We propose the use of wet chemical etching for fabricating inverted nanopyramids as a way to minimize the surface recombination velocities and maintain a conventional cell integration flow. In contrast to the broadly used plasma etching for nanopatterning, the wet chemically etched nanopatterning results in low surface recombination velocities, comparable with the state‐of‐the‐art random pyramid texturing. Applied to 40‐µm thick epitaxially grown crystalline silicon foils bonded to a glass carrier superstrate, the periodic‐inverted nanopyramids show carrier lifetimes comparable with the non‐textured reference foils ( τ eff = 250 µs). We estimate a maximum effective surface recombination velocity of 8 cm/s at the patterned surface, which is comparable with the state‐of‐the‐art values for crystalline silicon solar cells. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : We report on the optical and electrical performance of photonic nanostructures, prepared by nanoimprint lithography (NIL) and two etching routes: dry (dry‐NIL) and wet etching (wet‐NIL). These periodic nanostructures offer a lower integrated reflectance than the industrial random pyramid texturing. Applied to 40‐µm thick epitaxially grown crystalline silicon foils bonded to a glass carrier superstrate, the inverted nanopyramids (wet‐NIL) showed lifetimes comparable with the non‐textured reference foils ( τ eff = 250 µs) with a surface recombination velocity of 8 cm/s.